SCF CALCULATIONS FOR DETERMINING THE DIMENSIONS OF THE CENTRAL CAVITY Phthalocyanines p-EXTENDED without/with METALS - Cjuno H., Jesús A. (2005)
The electronic energy and geometric parameters have been calculated, for the Phthalocyanine (Pc), Naphthalocyanine (Nc), Anthracenocyanine (Anc), ZnPc, ZnNc, ZnAnc, CuPc, CuNc and CuAnc. Obtained the results with Hartree-Fock (RHF/6-31G *) calculations show that certain correlation exists between the size of the system p-extended and the distances of the internal cavity. A minimum variation of the dihedral angles exists showing in general a planar tendency in all the structures.